The Role of Nurses in the Treatment and Care of HIV/AIDS patients - based on the dimensions of health care. - Sinanaj, Glodiana; Harxhi, Arjan; Subashi, Brunilda (International Journal for Innovation Education and Research, 2018)
There is a lack of nursing studies that are specifically focused on assessing and caring for people living with HIV / AIDS to improve their quality of life. Little is known about the current situation regarding the care of persons living with HIV / AIDS.This cross-sectional, descriptive and analytical study will try to identify the assessment of nursing care in order to promote a better understanding of nursing care. A structured self-administered questionnaire administered from April 30 to June 15, 2014, was used for data collection.The participants were 55 patients, whose average age was 33.3 ±7.98 years, ranging from 20 to 55 years of age, out of which 24 (43.6%) of patients were female, while 31 (56.4% of them were males). They had different socioeconomic and educational levels. Regarding the biological dimension of nursing care, despite a positive trend in patient care estimation, differences between individual patient groups are observed based on the educational level.So patients with secondary and higher education are more likely to positively assess nursing care by the biological dimension versus 8-year-old patients. While with the psychological dimension and with other dimensions such as spiritual, social, stigmatization and discrimination there is no statistically significant relation between the socio-demographic characteristics of patients.Among the 5 dimensions, it is noticed that patients have evaluated less positively stigma, discrimination, compared to other dimensions. So patients are noticed a dissatisfaction with the fact that they are treated by nurses at the time of health care. The Nursing School to increase the development and implementation of quality research should identify the feelings, experiences, experiences and meanings of HIV/AIDS patients on nursing care. HIV / AIDS is a growing risk of modern times, requiring long-lasting research and research.